وعي أمهات الأطفال ذوي الاحتياجات الخاصة باستراتيجيات إدارة الضغوط وعلاقته بالتفاعل الأسري في ظل التعايش مع جائحة كوفيد-19 - مشعل، رباب السيد عبدالحميد; رصاص، نهاد علي بدوي (رابطة التربويين العرب, 2021)
يهدف البحث إلى دراسة العلاقة بين وعى أمهات الأطفال ذوي الاحتياجات الخاصة باستراتيجيات إدارة الضغوط بمحاورها (الإدارة الفعالة للضغوط-طلب المساندة الاجتماعي-مقاومة الرغبة في التجنب والانسجاب) والتفاعل الأسري في ظل التعايش مع جائحة كوفيد 19 بأبعاده (التفاعل بين الوالدين-التفاعل بين الأبناء-التفاعل بين الوالدين والأبناء). واتبع البحث المنهج الوصفي التحليلي، تم استخدام عدة أدوات هي استمارة البيانات العام، استبيان الوعي باستراتيجيات إدارة الضغوط في ظل التعايش مع جائحة كوفيد ١٩، استبيان التفاعل الأسري في ظل التعايش مع جائحة كوفيد ١٩. واشتملت عينة البحث على ١٠٧ من أمهات الأطفال ذوي الاحتياجات الخاص المترددات على مراكز الرعاية النهارية ومراكز العلاج الطبيعي بمحافظة المنوفية. وتم اختيار العينة بطريقة عمديه ويشترط أن تكون أم لطفل من ذوي الاحتياجات الخاصة، وبعد جمع البيانات تم تفريغها وجدولتها وتحليلها إحصائيا باستخدام برنامج SPSS. أظهرت النتائج وجود علاق ارتباطية موجبة دالة إحصائيا بين وعى أمهات الأطفال باستراتيجيات إدارة الضغوط بمحاورها والتفاعل الأسري في ظل التعايش مع جائحة كوفيد 19 بأبعادها عند مستوى معنوية 0,01، كما تبين وجود فروق دالة إحصائيا بين أمهات الأطفال ذوي الاحتياجات الخاصة الريفيات والحضريات في استراتيجيات إدارة الضغوط في ظل التعايش مع كوفيد ١٩ ومحورها (مقاومة الرغبة في التجنب والأنسجاب) وفي التفاعل الأسري وبعدي (التفاعل بين الوالدين-التفاعل بين الأبناء) عند مستوى معنويا عند مستوى 0,05 و 0,01 لصالح الحضريات عن الريفيات. لم توجد فروق بين الأمهات العاملات وغير العاملات في التفاعل الأسري بأبعاده، تفوقت العاملات عن غير العاملات في استراتيجيات إدارة الضغوط ف ظل التعايش مع كوفيد ١٩ ومحوريها (الإدارة الفعالة للضغوط-طلب المساندة الاجتماعية). لذا يوصى الجامعات والمراكز البحثية ومراكز خدمة المجتمع بتقديم الخدمات والبرامج الإرشادية من القوافل والندوات عن طريق الإنترنت الموجهة لأمهات الأطفال ذوي الاحتياجات الخاصة للتخفيف من حدة الضغوط وتنمية الوعي باستراتيجيات إدارة الضغوط. مع تحويل خدمات مراكز رعاية الأبناء من ذوي الاحتياجات الخاصة أسلوب خدماتها عن طريق الإنترنت وتقديم برامج تأهيليه وتدريبيه للأمهات والآباء كمساعدين للأخصائيين بما يمكنهم من متابعة البرنامج التأهيلي من المنزل.
The research aims to study the relationship between the awareness of mothers of children with special needs of stress management strategies with its axes (effective stress management - social support request - resistance to avoidance and withdrawal) and family interaction in light of coexistence with the Covid 19 pandemic in its dimensions (interaction between parents - interaction between children - interaction between parents and children). The research followed the descriptive analytical approach, several tools were used: the general data form, the questionnaire for awareness of stress management strategies in light of coexistence with the Covid 19 pandemic, the family interaction questionnaire in light of coexistence with the Covid 19 pandemic. The research sample included 107 mothers of children with special needs. Attending day care centers and physiotherapy centers in Menoufia Governorate. The sample was chosen in an intentional manner and it is required that it be the mother of a child with special needs, and after collecting the data, it was loaded, tabulated and statistically analyzed using the SPSS program. The results showed a positive, statistically significant correlation between the awareness of mothers of children of stress management strategies in its axes and family interaction considering coexistence with the Covid 19 pandemic with its dimensions at a significant level of 0.01, as it was found that there are statistically significant differences between mothers of children with special needs, rural and urban, in stress management strategies. Considering coexistence with Covid 19 and its axis (resisting the desire to avoid and withdraw) and in the family and dimensional interaction (interaction between parents - interaction between children) at a significant level at the level of 0.05. and 0.01. In favor of urban women over rural women. There were no differences between working and non-working mothers in the family interaction in its dimensions, the working women outperformed the non-working women in stress management strategies in light of coexistence with Covid 19 and its axes (effective stress management - requesting social support). Therefore, universities, research centers and community service centers are recommended to provide services and guidance programs from caravans and seminars via the Internet directed to mothers of children with special needs to alleviate stress and develop awareness of stress management strategies. With the transfer of the services of the centers for the care of children with special needs, their services through the Internet, and the provision of rehabilitation and training programs for mothers as assistance to specialists, enabling them to follow the rehabilitation program.
Keywords: ذوى الاحتياجات الخاصة -- التعايش السلمي -- التنشئة الأسرية -- جائحة كورونا "كوفيد-19"